2020
DOI: 10.1111/cea.13603
|View full text |Cite
|
Sign up to set email alerts
|

Non–heat inactivated autologous serum increases accuracy of in vitro CFSE lymphocyte proliferation test (LPT) for nickel

Abstract: Background: Skin patch testing is still seen as the gold standard for the diagnosis of allergic hypersensitivity. For several metals and for patients with a suspected adverse reaction to their medical device implant material, patch testing can be unreliable. The current alternative to metal allergy patch testing is the in vitro lymphocyte proliferation test (LPT) using tritiated thymidine. This method is well-established but requires handling of radioactive material, often uses heat-inactivated allogenic human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 40 publications
(56 reference statements)
2
23
0
Order By: Relevance
“…In agreement with this study, Spoerri et al 15 reported comparable sensitivity and specificity (75% vs 80%), respectively, of Ni‐specific Th cells as seen in this study (69% and 85%), using the same culture conditions and flow cytometric LPT analysis. By contrast, de Graaf et al 14 found a low sensitivity of 35% and high sensitivity of 93% of Ni‐specific Th cells, when culturing the cells in a medium with 10% heat‐inactivated serum. Furthermore, de Graaf et al 14 reported that in contrast to stimulation with various cytokine cocktails, nonheated inactivated autologous serum albumin resulted in 95% sensitivity and 93% specificity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In agreement with this study, Spoerri et al 15 reported comparable sensitivity and specificity (75% vs 80%), respectively, of Ni‐specific Th cells as seen in this study (69% and 85%), using the same culture conditions and flow cytometric LPT analysis. By contrast, de Graaf et al 14 found a low sensitivity of 35% and high sensitivity of 93% of Ni‐specific Th cells, when culturing the cells in a medium with 10% heat‐inactivated serum. Furthermore, de Graaf et al 14 reported that in contrast to stimulation with various cytokine cocktails, nonheated inactivated autologous serum albumin resulted in 95% sensitivity and 93% specificity.…”
Section: Discussionmentioning
confidence: 89%
“…By contrast, de Graaf et al 14 found a low sensitivity of 35% and high sensitivity of 93% of Ni‐specific Th cells, when culturing the cells in a medium with 10% heat‐inactivated serum. Furthermore, de Graaf et al 14 reported that in contrast to stimulation with various cytokine cocktails, nonheated inactivated autologous serum albumin resulted in 95% sensitivity and 93% specificity. The nonheated inactivated autologous serum is indeed an attractive approach to optimizing the LPT; however, the influencing factors in the allergic individuals' autologous serum are still unknown, making, for example, fluctuations of these factors a potential problem.…”
Section: Discussionmentioning
confidence: 89%
“…Conditions for T cell activation may be optimized. Besides, depletion of regulatory T cells (e.g., CD25+ T cells), addition of cytokines such as IL-12 or IL-4 or autologous serum may support the proliferation of chemical-specific T cell subsets [ 95 , 127 , 134 , 135 ]. In addition, the presence of co-stimulatory antibodies (e.g., α-CD28, α-CD49a) or checkpoint inhibitor antibodies (e.g., α-programmed death ligand 1/2 (PD-L1/2), α-PD-1, α-cytotoxic T-lymphocyte-associated protein (CTLA)-4) may optimize conditions for T cell activation [ 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…The challenge will be to remain above the elicitation threshold at noncytotoxic metal concentrations. Alternatively, focusing on in vitro lymphocyte cytokine and transformation tests which are showing promising results for identifying people with allergy to metals is an option 55,56 …”
Section: Discussionmentioning
confidence: 99%